A Study of Relationship between Personal Power Exercising of School Administrators and Teachers’ Performance Motivational Factors in Wangthong Educational Development Network 2 under Phitsanulok Primary Educational Service Area Office 2 - Sukchaona, Suthida; Wechayaluck, Nirada; Nak-ai, Nikom (Ratchaphruek Journal, 2024)
The purposes of this research were to study 1) the level of personal power exercised by school administrators, 2) the level of teachers' performance motivational factors, and 3) the relationship between the personal power exercised by school administrators and teachers' performance motivational factors in Wangthong Educational Development Network 2, under Phitsanulok Primary Educational Service Area Office 2. The sample consisted of 136 administrators and teachers in the Wangthong Educational Development Network 2. Administrators were 14 people and teachers were 122 people. They were selected by specific and stratified sampling methods. The instrument used for collecting data was a questionnaire with 5 rating scales, with reliability coefficients of 0.96 for part 1 and 0.95 for part 2. The statistics used for data analysis were mean, standard deviation, and Pearson product-moment correlation. The research findings were as follows: 1. The level of personal power exercised by school administrators was high in all aspects. The aspect with the highest average was referent power, followed by expert power. 2. The level of teachers' performance motivational factors was high in all aspects. The aspect with the highest average was the motivation factor, followed by the hygiene factor. 3. The overall relationship between the personal power exercised by school administrators and teachers' performance motivational factors was positively related to the research hypothesis, with a statistically significant level of .01. The highest correlation was between referent power and the hygiene factor.